(untitled) (International Seminar on Syariah and Law (INSLA), 2022)
Recently, the government has decided to exclude nicotine liquid from the Poisons Act 1952 (Act 366). This exclusion has led to the widespread and uncontrolled production and usage of nicotine. The retail value of the vape industry in Malaysia has surged by approximately 53 percent from RM2.27 billion in 2019 to an estimated RM3.48 billion in 2023. This study aims to identify the background of the exclusion of nicotine liquid from the Poisons Act 1952 (Act 366) and analyse the perspectives of Maqasid Al-Shariah on this exclusion. To obtain data, this research takes a qualitative approach utilizing document analysis, library research and interviews. The study’s findings indicate that the exemption of nicotine liquid from the Poisons Act 1952 (Act 366) contradicts with the principles of Maqasid Al-Shariah. It is crucial to emphasize education to enhance awareness that vaping is not a recreational alternative. Hence, every government decision or policy should be grounded in Maqasid Al-Shariah and Islamic principles. Further discussion and research about the exclusion of nicotine vape liquid from the Poisons Act 1952 (Act 366) from the perspectives of Maqasid Al-Shariah need to be conducted